2020
DOI: 10.21203/rs.3.rs-36655/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness Of Fiberoptic Phototherapy Compared To Conventional Phototherapy In Treating Hyperbilirubinemia Amongst Term Neonates: A Randomized Controlled Trial

Abstract: Background: Neonatal jaundice is one of the most common problems in newborns. Effective treatment of jaundice requires therapeutic intervention with phototherapy. Over recent years, several studies reported fiberoptic phototherapy to be less effective than conventional phototherapy in term neonates. Our study aimed to compare the effectiveness of fiberoptic phototherapy with a larger illuminated area and higher irradiance to conventional phototherapy methods. Methods: This was a randomized controlled trial con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…We evaluated 41 fulltext articles to check for eligibility, and, ultimately, 21 were included in this review. 3,15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The flowchart for evidence search and study selection is shown in ►Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We evaluated 41 fulltext articles to check for eligibility, and, ultimately, 21 were included in this review. 3,15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The flowchart for evidence search and study selection is shown in ►Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…15,[23][24][25] Fifteen articles compared LED devices with fluorescent lights. 3,[26][27][28][29][31][32][33][34][35][36][37][38]40,41 Two studies compared LED devices with halogen and fluorescent lights. 30,39 Five studies enrolled only full-term neonates 15,23,38,40,41 and 13 studies included infants over 35 or 36 weeks of gestation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations